Awareness of and attitudes towards skin‐cancer prevention: a survey of patients in the UK presenting to their general practice. (27th March 2013) - Butler, D. P.; Lloyd‐Lavery, A.; Archer, C. M. G.; Turner, R.
Summary: Background.  The rate of skin cancer in the UK continues to rise. Aim.  To identify the current knowledge and awareness of and attitudes towards the avoidance of skin cancer among a variety of patient groups to aid the design of future UK sun‐awareness campaigns. Methods.  Patients aged ≥ 16 years presenting to one of three general practices (two urban, one rural) in the UK during the period 1 June to 31 July 2010 were invited to complete a paper‐based questionnaire collecting data on their sun‐exposure behaviour, with significance assessed by the Fisher exact test. Results.  In total, 1000 patients (327 male, 673 female) responded. Those aged 16–30 years were significantly more likely to get sunburn than the older age groups. The understanding of ways to avoid skin cancer in 16–30‐year‐olds was also rated as significantly worse than that of all other age groups. Compared with the older age groups, this group was also less likely to avoid midday sun exposure ( P  < 0.001) or to cover up in the sun ( P  < 0.001). There was no significant difference in sun exposure or frequency of sunburn between those with or without a personal or family history of skin cancer. Those with a positive history were more likely to wear sunscreen ( P  < 0.01), but not to cover up or avoid the midday sun. Conclusions.  UK‐based sun‐awareness programmes should target younger age groups. In addition, healthcare professionals must ensure that opportunities are taken to reinforce the importance of safe sun exposure for patients presenting with skin cancer.